Network Pharmacology and Experimental Validation to Reveal the Pharmacological Mechanisms of Chongcaoyishen Decoction Against Chronic Kidney Disease - Fan, Zhenliang; Chen, Jingjing; Yang, Qiaorui; He, Jiabei (Frontiers in Molecular Biosciences, 2022)
Objective: To explore the pharmacological mechanisms of Chongcaoyishen Decoction (CCYSD) against chronic kidney disease (CKD) via network pharmacology analysis combined with experimental validation. Methods: We matched the active ingredients with gene targets and conducted regulatory networks through Perl5 and R 3.6.1. The network visualization analysis was performed by Cytoscape3.7.1, which contains ClueGO plug-in for GO and KEGG analysis. In vivo experiments were performed by 40 male SD rats, which were randomly divided into control group(n=10), sham group(n=10), UUO group(n=10) and CCYSD group(n=10). Tubulointerstitial fibrosis model was constructed by unilateral ureteral obstruction through the surgery and treated for 7 consecutive days with CCYSD(0.00657g/g/d). At the end of treatment, the rats were sacrificed and the serum and kidney were collected for further detection. Results: In total, 53 chemical compounds from CCYSD were identified and 12348 CKD-related targets were collected from the OMIM and GeneCards. A total of 130 shared targets of CCYSD and CKD were acquired by Venn diagram analysis. Functional enrichment analysis suggested that CCYSD might exert its pharmacological effects in multiple biological processes, including oxidative stress, apoptosis, inflammatory response, autophagy, and fiber synthesis et al., and the potential targets might be associated with JAK-STAT, PI3K-AKT, as well as other signaling pathways. The results of experiments revealed that the oxidative stress in the UUO group was significantly higher than that in normal state and was accompanied by severe tubulointerstitial fibrosis (TIF), which could be effectively reversed by CCYSD(P < 0.05).Meanwhile, aggravated mitochondrial injury and autophagy was observed in the epithelial cells of renal tubule in UUO group, compared to normal ones (P < 0.05), while the intervention of CCYSD could further activate the autophagy and reduce the mitochondrial injury (P < 0.05). Conclusion: We provide an integrative network pharmacology approach combined with in vivo experiments to explore the underlying mechanisms governing CCYSD treatment of CKD, which indicates that the relationship between CCYSD and CKD is related to its activation of autophagy, promotion of mitochondrial degradation and reduction of tissue oxidative stress injury, promoting the explanation and understanding of the biological mechanism of CCYSD .